Growth performance, carcass characteristics and cost benefit of feeding broilers with diets containing high quality cassava peel (HQCP) - Adekeye, Adetayo Bamikole; Amole, Tunde A.; Oladimeji, S.O.; Raji, A.A.; Odekunle, T.E.; Olasusi, O.; Bamidele, O. (Academic Journals, 2021)
A feeding trial was conducted to evaluate the effect of isonitrogenous and isocaloric diets containing varying levels of high-quality cassava peel (HQCP) fine mash on broilers’ performance, carcass characteristics, and cost benefit. A feeding trial was carried out using four hundred (400) 21-day old Arbor Acres broiler chicks weighing 570 – 630 g (live weight). The chicks were randomly allocated to five dietary treatments (T); (T1- 0 kg/t of HQCP, T2- 150 kg/t of HQCP, T3- 200 kg/t of HQCP, T4- 250 kg/t of HQCP and T5- 300 kg/t of HQCP) for 21 days in a completely randomized design. Data on live performance, carcass characteristics, and feeding costs were collected. The results showed significant (P<0.05) differences in final live weight, feed conversion ratio/feed efficiency ratio (FCR/FER), dressing percentage, total feed cost, and feed cost per weight gain across the treatments. T2 and T4 produced birds with the highest live weights of 2.08 and 1.98 kg, respectively. The dressing percentage ranged from 63.2% (T5) - 70.0% (T1). T5 had the lowest total feed cost (0.97 $/kg) while T2 had the lowest feed cost per body weight gain ($0.74), and best cost savings ($0.22). It was concluded that replacement of maize with 150 kg/t high quality cassava peel (HQCP) in broiler finisher diets improved production performance and save cost.